Exploring the impact of discharged patients’ characteristics on online health information-seeking behaviors: insights from patients’ dilemmas - Liu, Fei; Kong, Xiangyin; Xia, Tian; Guo, Huijing (Frontiers in Psychology, 2025)
IntroductionAligned with the dual-factor model, this study aims to investigate why discharged patients seek online health information, considering the complexity of patients’ dilemmas. Additionally, we account for specific cultural context factor in China and seek to examine the role of living with children in mitigating the dilemmas faced by discharged patients in their pursuit of additional online information.MethodsWe empirically tested the research model using data collected from 292 discharged patients. The data was examined through structural equation modeling, employing Smart PLS.ResultsThe findings suggest that perceived stress facilitates discharged patients’ engagement in seeking online health information, whereas resistance to change and learned helplessness impede such behaviors. Furthermore, our analysis reveals that cohabiting with children moderates the effects of resistance to change on online health information-seeking behavior.DiscussionIn conclusion, this paper extends the literature by examining the role of discharged patients’ characteristics on online health information-seeking behaviors. Following the practices in China, this study involves living arrangements (with children) as an essential factor in the research model. This paper offer suggestions to online providers to make health-related information more suitable for discharged patients.